The effect of highly-competitive exercises in the speed of competition in the development of rapid strength and the skill of Heri-Kushi-Auchi matt and the concentration of Hexokinase in the blood for young judo players - Yaqoob, Liza Rustum (International Journal of Psychosocial Rehabilitation, 2020)
Through the presence of the researcher in the field, being a former player and currently trained in the field of judo competition, and through careful observation of most training programs for some of the judo competition, I noticed that there is a problem in the field of training judo players, especially the youth category, where the research problem centered on missing training curricula for most of the judo competition Physical abilities and how to develop them, especially the fast power, because of its great importance for young judo players due to the lack of physical and technical skills training for the game, including the skill of Hari Kushi - Ogie Matt, as well as the great lack of exercise mechanism strongly competition speed and a lack of time allocated to it and in the knowledge of the role of indicators Functionality (enzymes) in the anaerobic process during their training units because of its importance to advance the numbers of the player physically and skillfully and focus on the correct performance and find appropriate solutions by following rapid exercises to know the extent of their impact on physical ability which is the rapid strength and ratio and skill of Heri Cauchy - Ogi matt an enzyme concentration hexactine in the blood, the importance of research involving the use of exercises strongly demonstrated the speed of the competitor It is in the development of rapid strength, the skill of Hi-Coche-Ogie Matt and the concentration of hexokinase in the blood for young judo players. The researcher adopted the experimental approach with equal groups and determined the research community (12 players) under the age of 20 years, and the program was implemented in exercises strongly the speed of competition for the rapid strength and the skill of Hari Kuchi-Ogie Matt and the ratio of concentration of hexokinase in the blood to the judo players for eight weeks and at the rate of three Training units per week, the researcher used the statistical bag (SPSS), and the researcher reached the most important conclusions that exercises strongly the speed of competition has positively affected the development of rapid strength and the skill of Hi-Coche-Ogie Matt and the ratio of concentration of hexokinase in the blood to Judo players young and recommends the researcher can rely on exercises strongly Rapid competition in developing all physical abilities and conducting similar studies on other age groups.